PERANCANGAN FIXTURE PADA PENGELASAN BODY ASSY ONE HAUL DI PT. UNITED TRACTORS PANDU ENGINEERING - , ARIF RAHMAN HAKIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT. United Tractors Pandu Engineering is a company specialized in the sector of industrial and construction, forestry and agro, oil and gas transport, attachments, Manufactur Original Equipment( OEM ) , and particularly in the mining sector. One Haul is one of the new and superior products at PT . United Tractors Pandu Engineering . Body is one component of a unit of One Haul, speeding up the process of weld setting and maintaining the critical point of body, is required tools such as jig and fixture. Because of that critical problem \"Perancangan Fixture Pada Pengelasan Body Assy One Haul di PT. United Tractors Pandu Engineeringâ is the title to be taken. This final project explores on a Design Body Assy One Haul Fixture For Setting Process Welding Body of One Haul Unit. The design of this fixture begins with the analysis of the product follow by 2D to 3D shape design connecting process continued with jigs strength analysis, calculation of material requirements, machining processes, monitoring up to the fixture release and finally ready for use . The next conducted the trial against the fixture . The author in this final project, calculate of the fixture strenght to withstand the whole load of products and included in the safe procedure. Also to be designed the construction of the fixture so as to maintain the critical point of the product and fixure practical which use by the operator . The concludes of the construction of the fixture body assy according to the design and work according to its function was done